An Outpatient Performance Improvement Project: A Baseline Assessment of Adherence to Pain Reassessment Standards. Issue 5 (1st May 2017) - Ross, Angela; Feider, Laura; Nahm, Eun-Shim; Staggers, Nancy
ABSTRACT: Background: This performance improvement (PI) project was conducted to recommend improvements for pain reassessment workflow and policies at a large military primary care clinic. The Joint Commission survey identified inconsistent pain reassessment practices at the facility in 2012. A review of the literature reveals that pain reassessment procedures can be affected by unclear organizational policies, poorly designed documentation procedures, and redundant or inefficient workflow practices. This PI project was designed to assess pain reassessment compliance rates, associated documentation, and clinic workflow, and to identify opportunities for improvement. Methods: Pain reassessment compliance was evaluated using an Electronic Medical Record (EMR) query for patients treated between February 1 and May 30, 2013, who received Toradol at a large military outpatient clinic ( n = 151). In addition, observations of clinic workflow were conducted using tracer methodology as recommended by The Joint Commission to track a convenience sample of 12 patients moving through clinic care processes. Pain reassessment documentation and workflow procedures were then evaluated using the Situation Awareness (SA) framework, which is an approach used to evaluate operational implications of factors affecting staff decisions and performance (e.g., stress and workload, interface design, automation, complexity of workflow, staff abilities and training, goals and expectations). Results: The EMR review revealed compliance rates greater than 90% for all pain reassessment requirements with the exception of the maximum 30-minute interval between initial and follow-up pain assessment required by clinic policy, which had a compliance rate of 38%. Pain reassessments were documented to occur at a mean time of 48.25 minutes after initial assessment. During the tracer, none of the 12 patient encounters was fully compliant with clinic policies. An analysis of clinic workflow using the SA framework revealed that the SA of clinic staff was impacted by a lack of standardized procedures and heavy reliance on staff memory. Discussion: Recommendations for improvement included possible extension of the 30-minute time requirement, development of a template for pain reassessment documentation in the EMR, standardizing hand off and admission/discharge processes, and designing an electronic or manual dashboard to indicate pain reassessment times. Future PI projects in other military clinics would benefit from use of the SA perspective to review clinic policies, EMR documentation, and workflow analysis. Further analysis will be needed to evaluate the impact of these improvements.